Workplace and rehabilitation-based approaches to enhancing long-term wellbeing and physical activity in sedentary populations - Montney, Justin Luke (My University, 2025)
OBJECTIVE: Long-term adherence to physical activity (PA) following worksite or clinical interventions typically diminishes over time, stemming from a critical gap between theory-based program design and real-world implementation feasibility. While research shows that long-term adherence is driven by the value of short-term intrinsic rewards like improved mood, self-efficacy, and feelings of accomplishment, most interventions fail to bridge the gap between this knowledge and real-world practice. Therefore, the purpose of this dissertation is to examine the barriers and facilitators of implementing PA interventions in sedentary populations from the multiple perspectives of the existing literature, employee participants, and clinical providers, while exploring how practical implementation factors—specifically, perceived benefits, program simplicity, adaptability, and user burden—impact feasibility. METHODS/RESULTS: The first paper, a systematic review of worksite PA programs (N=8 studies), examined their effects on PA, sedentary behavior (SB), and occupational wellbeing. The review found that all 8 interventions reported improvements in PA or SB, with the most common wellbeing benefits being improved energy (reported in 62.5% of studies), reduced fatigue (reported in 50% of studies), and reduced work absenteeism (reported in 37.5% of studies). The most promising results were observed in multi-component interventions that incorporated both equipment and education/behavioral support. The second paper reports on a social ecological model-based 8-week pilot randomized controlled trial (N=36) which found that a walking intervention was as effective as a novel, culturally-adapted Radio Taiso (RT) routine, a form of Japanese synchronized music and rhythm based calisthenics, in reducing objective sedentary time (main effect of Time, F(2, 25.9) = 12.06, p < .001). Additionally, the simpler walking intervention resulted in significantly higher implementation fidelity from an employee perspective and reported more qualitative enjoyability factors. The third paper details a mixed-methods implementation study of a novel, Health Action Process Approach (HAPA)-based "Cardio Commitment Course" (C3) within cardiac rehabilitation (N=9 staff). Staff attended a 4-week training intervention consisting of live, interactive sessions on HAPA theory, examples of how to use the program's educational tools, and expert-led guidance for motivational interviewing and conducting group education. This study revealed that while the training produced a large and significant improvement in staff confidence for key areas (e.g., setting goals with patients, p = .018, Cohen's d = 0.79), program complexity and time constraints were significant barriers that hindered implementation fidelity, with only 20% of patients receiving the target number of educational sessions from the provider perspective. CONCLUSION: Collectively, these studies demonstrate that the value of theory-based programs is realized only when they are designed to be simple, adaptable, and place a low burden on both participants and providers. Successful implementation requires prioritizing simplicity, adaptability, and low participant and provider burden to achieve sustained engagement and positive outcomes in both worksite and clinical environments.
Keywords: Cardiac rehabilitation; Health action process approach; Implementation science; Physical activity; Sedentary behavior; Self-efficacy theory; Worksite wellness